Biliopancreatic diversion with duodenal switch modifies plasma chemerin in early and late post‐operative periods. (9th May 2015) - Parlee, Sebastian D.; Wang, Yan; Poirier, Paul; Lapointe, Marc; Martin, Julie; Bastien, Marjorie; Cianflone, Katherine; Goralski, Kerry. B.
<x xml:space="preserve">Abstract</x> Objective Bariatric surgery remains the most effective treatment for obesity and metabolic syndrome. Surgical benefit arises from early‐phase resolution of hyperglycemia and late‐phase weight loss. The adipokine chemerin is of interest given its roles in immunity, adipogenesis, and metabolism. The study objective was to examine the effects of biliopancreatic diversion with duodenal switch (BPD‐DS) on plasma chemerin in the early and late post‐operative stages. Methods 83 adults with obesity undergoing BPD‐DS, 45 obese non‐surgical controls, and 9 lean surgical controls were enrolled. Plasma parameters and anthropometric measures were obtained at baseline and at, early (24 h, 5 D) and late (6 months and 12 months) post‐operative stages. Results Plasma chemerin dropped from 176±49 ng/mL at baseline to 132±52 ng/mL 24 h after BPD‐DS, rebounded to 200±66 ng/mL after 5 D, and declined to 124±51 and 110±34 ng/mL after 6 and 12 months. Plasma chemerin correlated negatively with measures of inflammation and hepatic injury and positively with measures of obesity, metabolic syndrome, and inflammation in the early and late post‐operative periods, respectively. Conclusions Chemerin has a novel role in surgical injury but not hyperglycemia resolution early after BPD‐DS. Over the long term, plasma chemerin declines to a new set point that is partially determined by body fat reductions.